Why do farmers expand their land into forests?: theories and evidence form Tanzania - Angelsen, A.; Shitindi, E.F.K.; Aarrestad, Johnstein (1999)
This paper examines the causes of agricultural land expansion and deforetstion in Tanzania. In the theoretical section, two different -- and partly contradicting -- sets of hypotheses are outlined. These are based on a subsistence approach, emphasising the food or income requirements of farm household, and a market approach, focussing on the relative profitability of agriculture. The statistical analysis shows that increased agricultural output prices, in particular for annual crops, is a major factor behind agricultural expansion. An increase of 1 per cent output prices leads to about 1 per cent increase in agricultural area. Other factors such as input prices, technology and economic growth are tested and discussed, but the conclusions are less robust. The controversial role of population growth in expalining deforestation is addressed. Generally the results lend support to the market rather than the subsistence approach.